Формирование профессиональной культуры будущего специалиста технического профиля - Грень, Лариса Николаевна; Курбанова, Х. Ш. (НТУ "ХПИ", 2015)
В статье раскрыта сущность культуры как конкретно- исторического явления, тесно связанного с понятием «профессиональная культура», раскрыто содержание профессиональной культуры специалиста как системного образования, очерчены компоненты профессиональной культуры и даны их характеристики. Показана роль преподавателя в формировании профессиональной культуры будущего специалиста, необходимая в дальнейшей жизни и деятельности.

The article shows the essence of culture as a concrete social-andhistorical phenomenon closely linked with the notion of professional culture; the content of professional specialist’s culture as a system formation is disclosed; also components of professional culture are outlined and their characteristics are given. The teacher’s role in forming professional culture of a future specialist needed in further life and activity is shown as well.
Forming the culture of a future technical specialists
Keywords: деятельность; профессионализм; личностные компоненты; показатели; профессиональное мастерство; студенты; уровень развития; culture; activity; professional culture; professionalism; personal components; indices; level; competence; professional skill; students; future technical specialist